Acceptability of Time-Limited Eating in Pediatric Weight Management - Tucker, Jared M.; Siegel, Robert; Murray, Pamela J.; Han, Joan C.; Boyer, Katherine; Reed, Nichole; Allenby, Taylor; Novick, Marsha (Frontiers in Endocrinology, 2022)
Background: Adherence to dietary interventions is a significant barrier in the treatment of childhood obesity. Time-limited eating (TLE) is a simple dietary approach that limits food intake to a given number of consecutive hours per day, but parental and youth acceptability of TLE in youth with obesity is unknown. This study explored the feasibility of utilizing TLE among parents and youth attending pediatric weight management (PWM). Methods: Members of COMPASS (Childhood Obesity Multi-Program Analysis and Study System) developed a survey to assess the acceptability of TLE in families attending PWM, which included patient characteristics, current diet and sleep schedules, and interests in trying TLE. The survey was administered electronically via REDCap or manually to parents of patients between the ages of 8-17 years old attending one of five PWM practices in the COMPASS network. Results: Patients (n=213) were 13.0 ± 2.5 years old, 58% female, 52% White, 22% Black, 17% Hispanic/Latino, and 47% reported a diagnosed psychological disorder. On average, parents reported their child’s daily eating spanned 12.5 ± 1.9 hours (7:35am - 8:05pm) and included 5.6 ± 1.6 eating bouts (meals + snacks). Most parents reported being likely to try TLE ≤12 hours/d (TLE12: 66%), which was similar to the likelihood of following a nutrient-balanced diet (59%). Likelihood was lower for TLE ≤10 hours/d (TLE10: 39%) or ≤8 hours/d (TLE8: 26%) (p<0.001 for both). Interest in TLE was not consistently related to patient age, sex, or ethnicity, but was lower in patients with a psychiatric diagnosis vs. no diagnosis (TLE8: 19% vs. 32%; p=0.034). Patients of parents who reported being likely to try TLE, compared to those unlikely to try TLE, had shorter eating windows (p<0.001) and ate fewer snacks (p=0.006). Conclusions: Two-thirds of parents with children attending PWM programs report interest in TLE ≤12 hours/d regardless of demographic characteristics, but interest wanes when limiting eating to ≤10 or ≤8 hours per day. Time-limited eating appears to be a feasible option in PWM settings provided treatment options are individualized based on the interests and barriers of patients and their families.